2018
DOI: 10.1016/j.cell.2018.09.047
|View full text |Cite
|
Sign up to set email alerts
|

The NLRP6 Inflammasome Recognizes Lipoteichoic Acid and Regulates Gram-Positive Pathogen Infection

Abstract: SUMMARY The activator and composition of the NLRP6 inflammasome remain poorly understood. We find that lipoteichoic acid (LTA), a molecule produced by Gram-positive bacteria, binds and activates NLRP6. In response to cytosolic LTA or infection with Listeria monocytogenes, NLRP6 recruited caspase-11 and caspase-1 via the adaptor ASC. NLRP6 activation by LTA induced processing of caspase-11, which promoted caspase-1 activation and IL-1β/IL-18 maturation in macrophages. Nlrp6−/− and Casp11−/− mice were less susce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
231
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 212 publications
(242 citation statements)
references
References 78 publications
(113 reference statements)
6
231
0
Order By: Relevance
“…Although earlier reports indicated that CASP11 has no role in protection against L. monocytogenes infection , casp11 −/− mice were recently demonstrated to have improved survival rates and lower bacterial loads in response to intravenously delivered L. monocytogenes as well as S. aureus 8325‐4 , indicating that the absence of CASP11 helps with the clearance of some Gram‐positive bacteria. To investigate the impact of CASP11 on bacterial pulmonary loads, we intratracheally infected WT and casp11 −/− mice with 2.5 × 10 8 CFU of MRSA and determined the bacterial burden at 96 h post‐infection.…”
Section: Resultsmentioning
confidence: 96%
“…Although earlier reports indicated that CASP11 has no role in protection against L. monocytogenes infection , casp11 −/− mice were recently demonstrated to have improved survival rates and lower bacterial loads in response to intravenously delivered L. monocytogenes as well as S. aureus 8325‐4 , indicating that the absence of CASP11 helps with the clearance of some Gram‐positive bacteria. To investigate the impact of CASP11 on bacterial pulmonary loads, we intratracheally infected WT and casp11 −/− mice with 2.5 × 10 8 CFU of MRSA and determined the bacterial burden at 96 h post‐infection.…”
Section: Resultsmentioning
confidence: 96%
“…In a human embryonic kidney cell line, overexpressed NLRP6 has been shown to co‐precipitate with overexpressed caspase‐1 and ASC (Levy et al, ). Similarly, the pyrin domain of NLRP6 has been shown to interact with ASC in a purified protein system (Shen et al, ), whereas a recent study in myeloid cells argues that NLRP6 forms a heterogenous inflammasome with ASC, caspase‐1, and caspase‐11, which responds to lipoteichoic acid, a major constituent of the Gram‐positive bacterial cell wall (Hara et al, ; Figure ). Whether lipoteichoic acid stimulates NLRP6 in IECs remains to be determined.…”
Section: A General Overview Of Inflammasomesmentioning
confidence: 99%
“…To validate the interactions determined by SAW, we used NMR spectroscopy to test the specific binding of PPE 1 , LTA, LPS, and Kdo 2 to Bet_v_1 (Table , Figure ). Substantial differences between theH‐N HSQC spectra of N‐labeled Bet_v_1 in the absence and presence of PPE 1 confirmed that the allergen specifically binds PPE 1 . The K d was consistent with a low to sub‐µmol/Laffinity, but intermediate exchange and a poor signal‐to‐noise ratio prevented direct measurement.…”
Section: Resultsmentioning
confidence: 86%
“…Other ligands of interest include deoxycholate (DOC), a secondary bile acid generated as a microbial metabolic byproduct that is structurally similar to brassinosteroids and serves as an established model ligand for Bet_v_1 . In addition, immunomodulatory microbial compounds (such as the TLR2 and NLRP6 agonist lipoteichoic acid, LTA, and the endotoxin lipopolysaccharide, LPS) have been proposed to interact with Bet_v_1 …”
Section: Introductionmentioning
confidence: 99%